Reading and Writing in the English Language: A Pre-requisite for Farm Productivity and Food Security Among Women Farmers in Imo State, Nigeria - Nwulu, F.N; Obinna, V.O; Chukwu, K.U; Okere, M.C; Mbarah, G.O; Emeka, D.N; Onuegwunwoke, C.A; Amadi, G.U; Anuonye, F.D; Nzeakor, N.C; et al. (The Bioscan, 2026)
Literacy is important in all areas of human endeavor, including farming/agriculture. Farm people especially women who spend most of their times feeding families need to read and write to perform in the occupation of farming. The paper investigates the influence of reading and writing English Language for increased farm productivity and food security. Multi-stage sampling technique was used in selecting a total of 120 women farmers from various communities of Imo State, Nigeria. Questionnaire and oral interview were used to collect data from the respondents. Descriptive tools were used to analyze data. Results showed a moderate level of literacy among the women as seen in ability to fill agricultural forms in English (M=2.33), ability to read & understand farm manuals (M=2.45) and confidence in speaking English (M=2.39). Literacy influence farm productivity when a farmer reads farm manuals and applies the instruction (M=3.08), contributes to better farm decisions (M=3.15), improves farm planning (M=3.00), adopts modern farm techniques (M=3.12), prevents misuse of chemicals (M=3.09). Women with higher literacy understands training manuals (M=3.08), engages actively during workshops/seminars (M=3.10), understands weather information (M=3.07), reduces risks of misinformation (M=3.15). Literacy also influence food security by avoidance of food wastages (M=3.34), improves resilience and food stability (M=3.40), improves dietary quality and household health (M=2.38), leads to higher income (M=3.33), promotes household food distribution (M=3.39). The challenges facing women farmers due to limited literacy includes: limited access to agricultural information (38.2%), limited opportunity to participate in programmes (25.3%), difficulty accessing credit (24.1%), poor communication skills (54.1%), limited market access (30.8%). To address the challenges, adult literacy programs, use of indigenous languages, formation of cooperatives, and capacity building for empowerment be pursued vigorously.